Barium cycling in the Gulf of Aqaba - Mayfield, Kimberley K.; Horner, Tristan J.; Torfstein, Adi; Auro, Maureen E.; Crockford, Peter W.; Paytan, Adina (Frontiers in Earth Science, 2024)
The isotopic composition of barium (δ138Ba) has emerged as a powerful tracer of deep-ocean circulation, water mass provenance, and the oceanic Ba cycle. Although the δ138Ba of water masses is primarily controlled by the balance between pelagic barite precipitation and Ba resupply from ocean circulation, questions remain regarding the isotope offset associated with pelagic barite formation and how the resultant Ba isotope compositions are transmitted through the water column to marine sediments. To address these questions, we conducted a time series study of dissolved, particulate, and sedimentary Ba chemistry in the Gulf of Aqaba (GOA), in the northern Red Sea, from January 2015 to April 2016. These data span significant seasonal changes in hydrography, primary productivity, and aerosol deposition, revealing three principal findings. First, the dissolved Ba chemistry of the GOA is vertically uniform across the time series, largely reflecting water mass advection from the Red Sea, with mean dissolved Ba concentrations of 47.9±4.7 nmol kg−1 and mean δ138Ba = +0.55±0.07 ‰ (±2 SD, n = 18). Second, despite significant variations in particulate matter composition and flux, the δ138Ba of sinking particulate Ba maintained a consistent isotope composition across different depths and over time at +0.09±0.06 ‰ (n = 26). Consequently, these data imply a consistent Ba isotope offset of −0.46±0.10 ‰ (±2 SD) between sinking particulates and seawater. This offset is similar to those determined in previous studies and indicates that it applies to particulates formed across diverse environmental conditions. Third, barite-containing sediment samples deposited in the GOA exhibit δ138Ba = +0.34±0.03 ‰, which is offset by approximately +0.2 ‰ relative to sinking particles. While the specific mechanism driving this offset remains unresolved, our results highlight the importance of performing site-specific proxy validations and exercising careful site selection when applying novel paleoceanographic proxies.